#TITLE_ALTERNATIVE# - PERMATA ISTIMELATI (NIM 10105072); Pembimbing: Dr. Agus Yodi Gunawan, ATIKA
The presence of condensate films in a gas transmission pipeline may decrease the delivery of the gas rate, the condensate will form thin layer, which tends to gag the flow. One of the techniques to overcome this problem is to add surfactants to the gas flow. The effect of the surfactant is to decrease the surface tension at the interface between condensate layer and gas. The presence of surfactant will serve not only to balance the normal but also the tangential stresses. Since the condensate film occurred in the pipeline are very viscous, and the gas stream is assumed to influence the film on its surface only, the model then leads to a Newtonian fluid model with small Reynolds number. Using dimensional analysis and Lubrication approximation we are led to the dynamic equation of the condensate surface. We shall focus on studying the effect of the insoluble surfactant on the rupture of a condensate thin film by means of linear stability analysis and nonlinear analysis (numerical simulations). The linear stability analysis indicates that the (in)stability of the system mainly depends on the magnitudes of surfactant concentration, the surface tension, Van der Waals force, and wind stress. When the surfactant is not present, the wind stress does not affect the stability of the system. It only contributes to the imaginary part of the growth rate of the disturbances, not to its real part. However, when the surfactant and the wind stress are both present, they affect (the instability) of the condensate surface; the condensate surface becomes unstable. The instability of the condensate thin films indicates that the condensate may be able to be lifted up by the gas flow.